Representation of Different Sorting Algorithms Using Sorting Visualizer (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The most effective way to sort elements (data) significantly impacts how quickly a computer can complete a task. The sorting algorithm is one of computer science’s most important areas of study. It is the process of arranging unorganized elements in an organized manner. The main goal is to make records easier to search, sort, insert, and delete. Through the description of the existing five sorting algorithms: Bubble, Selection, Insertion, Merge, and Quick Sort, the Time and Space Complexity are determined. Time complexity varies as Best Case(O), Average Case(Θ), and Worst Case(Ω). Here in sorting, the Worst Case complexity is O(n2), and the Best Case complexity is O(n log n), where "n" represents the number of elements(data) in the array. This project consists of a UI-based web application that can visualize the sorting process using various colors and denote the status of the elements of the array.